The Effect of Job Satisfaction and Organizational Commitment on Turnover Intention at BETA BERLIAN MANADO - Dea U Waworuntu; S.L.H.V Joyce Lapian; Merinda Pandowo (Universitas Sam Ratulangi, 2022)
This study aims to examine the effect of simultaneous and partial of job satisfaction, organizational commitment as an independent variable on turnover intention as the dependent variable. The methodology of this research uses quantitative descriptive. The sampling technique using simple random sampling obtained a sample of 52 employees of BETA BERLIAN MANADO. Data collection using a questionnaire while the data analysis method used is multiple linear regression analysis processed with the help of SPSS version 25. The results showed: (1) F test results showed that job satisfaction, organizational commitment and work environment simultaneously had a positive and significant effect on turnover intention at BETA BERLIAN MANADO. (2) Based on the partial test results the job satisfaction variable has a negative and significant effect on turnover intention at BETA BERLIAN MANADO. (3) Based on the partial test results the organizational commitment variable has a negative and not significant effect on turnover intention at BETA BERLIAN MANADO.